Impact of depression on the academic performance of international students in Udayana University - Jacintha James; AA. Sagung Sawitri; Luh Putu Ariastuti; Putu Aryani (Intisari Sains Medis, 2019)
Background: Depression is a mental disorder that affects an individualâ€™s mood and emotion. Depression is very common among the students. In this study, the impact of depression, especially on the academic performance of students who are abroad, studies along with the risk factors of depression.Aim: The study aims to know the relationship between depression and the academic performances of international students studying abroad. Â Method: In this analytic study, a cross sectional method was being used. This method is being used to analyze the relationship between the factors that influence the academic performance and also to investigate the relationship between depression and academic performance of the students.Result: As for the residence factor, the student who was lived alone performed better in academic. For the method of study factor, the student who conducts independent learning performs well in academic whereas for the factor back to Malaysia in a year, the students who go back to Malaysia less than or twice a year performs better in their academic. As for the family support factor, students who have good family support obtain good results in academic performance, but for factor family financial support, students with inadequate financial support obtain good results in their academic.